Is trade relevant to the macro drivers of carbon dioxide emissions? A study of high- and low-trade openness economies - Suleman, Shahida; Mohd Thas Thaker, Hassanudin; Cheong, Calvin Wing Hoh (John Wiley & Sons, 2025)
The objective of this research is to systematically compare the impact of macro determinants on CO2 emissions, using the theoretical frameworks of trade, the Environmental Kuznets Curve, and the Pollution Haven Hypothesis. The study specifically focuses on high- and low-trade-openness economies from 1995 to 2020. Methodologies employed include stepwise regression, fully modified least squares, pooled ordinary least squares, and fixed effects models. Long-run dynamics were assessed using Granger causality tests and Pedroni and Johansen cointegration tests. The results indicate both long-term and short-term relationships between CO2 emissions and the following variables: (i) gross capital formation (GCF), (ii) per capita income (PCI), (iii) population (POP), and (iv) trade openness. Trade openness has a positive and significant effect on CO2 emissions in highly trade openness economies, whereas it has a negative effect in low trade-open economies. Highly open economies are more significantly impacted by GCF and POP on CO2 emissions compared with low- trade openness economies. Additionally, PCI positively and significantly influences CO2 emissions in low- trade openness countries, and this effect is greater than in high- trade openness economies. The study also identifies a bidirectional causal relationship between PCI, GCF, and CO2 emissions in both groups of economies, as well as a unidirectional relationship between trade openness, POP, and CO2 emissions in both high- and low- trade openness countries